On the understanding of fairness among professional soccer Players-a reconstructive study of the interpretation of fairness norms - Kathrin Wahnschaffe-Waldhoff (Bern Open Publishing, 2023)
Introduction In professional soccer, success and fairness norms can come into conflict in many situations. This is why individual actors must constantly weigh one against the another. From a sociological perspective, this does not involve an antagonism between the validity and non-validity of a specific norm but rather a fluent transition from one to the other and conflicting norms can claim validity at the same time (Weber, 2008, p. 23). The current state of research has shown that increasing competitive pressure has given rise to a tendency to seek tactical advantages and deliberately violate norms in professionalized and commercialized sports in general (Lenk, 2014) and that the high pressure to succeed has resulted in an increasing deviation from fairness norms in professional soccer in particular. Bohle and Stallberg (1998) even speak of the compulsion to deviate and the normality of violating norms, which partly results in severe fouls and injuries. Moreover, many studies explicitly or implicitly share the assumption that processes of commercialization tend to suspend norms of fair play (Renson, 2009, Whysall, 2014). At the same time, sports actors do indeed make reference to the validity of certain principles of fairness (Wilke 2009). What appears to be a discrepancy, raises the important question of what the actors actually mean when they speak of fairness. Research so far has offered few answers to this question and has above all addressed youth and amateur soccer. This research gap with respect to professional soccer is at odds with the significance of high-performance soccer to athletics and society, a gap that this reconstructive study has set out to close. Methodology This study employed qualitative, narrative interviews in the vein of grounded theory to reconstruct, empirically and systematically, interpretive patterns of fairness and unfairness from the perspective of professional soccer players. The analyses applied coding procedures in accordance with Strauss and Corbin (1998). Results The study shows that the players do view fairness values as desirable in principle, yet do not draw on them in orienting their own action. Thus, these values do not serve to derive fairness norms. What we see furthermore is that considerations of fairness are clearly dominated by an orientation toward success, which players experience as imperative on all levels. The key, and new, insight is that the players interpret the concept of fairness in a much broader sense than has been discussed in sports science discourse thus far, where fairness is mainly considered in the context of competitive situations. The players, by contrast, clearly distinguish between the settings of competition (on game day), practice, and interaction with others off the field. References Bohle, H. H., & Stallberg, F. W. (1998). Erfolgsdruck und strategische Devianz. Zur Normalität von Anomie im modernen Profifußball [Pressure to succeed and strategic deviance. On the normality of anomie in modern professional football]. Soziale Probleme, 9, 51-89. Lenk, H. (2014). Sportethik und Wirtschaftsethik: Konkurrenz und Fairness in Sport und Wirtschaft [Sport ethics and business ethics: Competition and fairness in sport and business]. In M. Maring (Hrsg.), Bereichsethiken im interdisziplinären Dialog. KIT Scientific Publishing. http://books.openedition.org/ksp/3134 Renson, R. (2009). Fair play: Its origins and meanings in sport and society. Kinesiology, 41(1), 5-18. Wahnschaffe-Waldhoff, K. & Mutz, M. (2021). Aneignung und Auslegung von Fairnessnormen im Fußball: eine qualitative Studie mit Profifußballspielern [Appropriation and interpretation of fairness norms in football: A qualitative study with professional football players]. Zeitschrift für Soziologie der Erziehung und Sozialisation, 41(2), 144-164. Weber, M. (2008). Wirtschaft und Gesellschaft [Economy and society]. Wunderkammer. Whysall, P. (2014). Reflections on ethics, sport and the consequences of professionalization. Business Ethics 23(4), 416-429. Wilke, M. (2009). Das Ende der Fairness? Ethische Werte aus dem Sport im Spiegel der Gesellschaft [The end of fairness? Ethical values from sport in the mirror of society]. [Doctoral dissertation]. Deutsche Sporthochschule Köln.